2018
DOI: 10.1371/journal.pone.0196062
|View full text |Cite
|
Sign up to set email alerts
|

Earlier time to aerobic exercise is associated with faster recovery following acute sport concussion

Abstract: ObjectiveTo determine whether earlier time to initiation of aerobic exercise following acute concussion is associated with time to full return to (1) sport and (2) school or work.MethodsA retrospective stratified propensity score survival analysis of acute (≤14 days) concussion was used to determine whether time (days) to initiation of aerobic exercise post-concussion was associated with, both, time (days) to full return to (1) sport and (2) school or work.ResultsA total of 253 acute concussions [median (IQR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 34 publications
(60 reference statements)
3
110
2
Order By: Relevance
“…Although outside the scope of this study, multiple authors have demonstrated that symptom‐limited aerobic exercise aids recovery of post‐concussive symptoms 70,73‐76,78‐83 . The rationale for potential benefit of exercise post‐injury is outlined in prior animal and human studies.…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
See 2 more Smart Citations
“…Although outside the scope of this study, multiple authors have demonstrated that symptom‐limited aerobic exercise aids recovery of post‐concussive symptoms 70,73‐76,78‐83 . The rationale for potential benefit of exercise post‐injury is outlined in prior animal and human studies.…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…If symptom freedom is not an achievable goal, and we aim for “symptom stability” how does one reconcile this with existing consensus guidelines and state regulations regarding medical clearance for sport? 31,62‐64 There is a paucity of evidence to support the idea that ongoing inactivity or rest aids recovery and prevents re‐injury beyond the acute window of vulnerability (>~10 days) 31,78,79,101,102 . In fact, we know that exercise actually aids recovery of post‐concussive symptoms 70,73‐76,78‐83 and helps in management of primary headache disorders, such as migraine (see below). How should we approach the development of a new or worsened headache post‐injury in an adolescent with the goal of return to sport?…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
See 1 more Smart Citation
“…14 • One article 15 demonstrated that initiating aerobic exercise had a positive effect on returning to school/work and sport sooner rather than delayed exercise. • All 5 articles [14][15][16][17][18] demonstrated that implementing early controlled aerobic exercise did not have a detrimental effect on recovery. • One article 17 demonstrated that although the early implementation of controlled aerobic exercise resulted in temporary increases in symptoms, it did not lengthen the overall duration of symptoms and the number of days to return-to-play.…”
Section: Summary Of Search Best Evidence Appraised and Key Findingsmentioning
confidence: 99%
“…5 Based upon 2 articles included in this review, early controlled aerobic exercise initiated within 3 to 11 days postconcussion is safe but may not be effective at decreasing symptom duration and overall recovery. 17,18 The other 3 studies demonstrated early controlled aerobic exercise from 3 to 6 days postinjury had a positive effect, [14][15][16] meaning the earlier one started exercise the quicker the symptom resolution within the first 2 weeks. These findings may encourage a shift in current rehabilitation techniques from a conservative, rest-centered approach to a more active and progressive approach.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%